SMYD3 overexpression indicates poor prognosis and promotes cell proliferation, migration and invasion in non-small cell lung cancer - Li, Jing (Int J Oncol, 2020)
SET and MYND domain-containing protein 3 (SMYD3) is a lysine methyltransferase, and its aberrant expression has been implicated in several malignancies. However, its clinical and biological roles in non-small cell lung cancer (NSCLC) remain unclear. In the present study, it was revealed that SMYD3 was significantly upregulated in NSCLC tissues, as compared with paired adjacent normal tissues. A high SMYD3 expression was associated with aggressive clinicopathological characteristics, as well as poor disease-free survival and overall survival (OS) in NSCLC patients. Multivariate analysis revealed that SMYD3 overexpression was an independent predictor of poor OS in NSCLC patients. In addition, SMYD3 knockdown inhibited cell proliferation, triggered apoptosis, and blocked migration and invasion in NSCLC cells in vitro, whereas stable SMYD3 overexpression promoted NSCLC cell proliferation. Furthermore, the SMYD3-silenced NSCLC cells became more sensitive, whereas the SMYD3-overexpressed NSCLC cells became more resistant to the apoptosis induced by cisplatin. Mechanistic analysis revealed that SMYD3 knockdown led to the upregulation of Bim, Bak and Bax, and the downregulation of Bcl-2, Bcl-xl, MMP-2 and MMP-9 in NSCLC cells. In combination, the present findings indicated that SMYD3 has oncogenic potential in the context of NSCLC, providing evidence that may be exploited for both prognostic and therapeutic purposes in the future.